Promoting Health Education through Effective Communication for Development - Udoudom, Uduak; Igiri, Anthony; George, Kufre; Aruku, Kalita Joseph (Lembaga Yasin AlSys, 2024)
This conceptual research explores the pivotal role of effective communication in advancing health education for development. By examining the symbiotic relationship between communication strategies and health promotion, it unveils the potential to empower individuals and communities with the knowledge and tools necessary for healthier lives. Through an interdisciplinary approach, the study aims to elucidate how tailored communication methods, including digital platforms, social marketing, and culturally sensitive messaging, can enhance the dissemination of health information, influence behaviour change, and ultimately contribute to the holistic development of societies. In a world where health challenges remain prevalent, this research underscores the imperative of cultivating a dynamic and responsive communication framework to foster sustainable improvements in global public health.